A Comparative Analysis of Metonymy, Meronymy, and Polysemy in English and Sindhi Languages (Journal of Asian Development Studies, 2026)
The study aimed to comparatively analyse metonymy, meronymy, and polysemy in English and Sindhi by documenting the metonymous, meronymous, and polysemous nature of words in both languages. Metonymy, meronymy, and polysemy are important aspects of language that play an essential role in understanding how words are associated with different objects and how multiple meanings are acquired. These linguistic phenomena are examined to explore the similarities and differences between the two languages with reference to these semantic relationships. The methodology adopted a qualitative analysis. The data was collected from a diverse corpus of English and Sindhi texts. The findings illustrated the ways in which metonymy, meronymy and polysemy are employed in these languages, elucidating their cultural and linguistic nuances. This study will also contribute to the understanding of the Sindhi language in the broader global linguistic context. It will also encourage further research on such linguistic devices in other languages.